Pembelajaran Seni Lukis Menggunakan Cat Akrilik dengan Teknik Plakat di Kelas VIII Ignatius Global School Palembang: Penelitian - Rika Dwi Oktavia; Dedy Firmansyah; Silo Siswanto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study is the background of the importance of understanding how painting teachers integrate acrylic paint techniques in the learning process. This study aims to explore how the strategies used in teaching are used by teachers and their impact on students in painting. So this study is entitled "Learning Painting Using Acrylic Paint With Plaque Techniques in Class VIII Ignatius Global School Palembang". The purpose of the study is to describe the process of learning painting using acrylic paint with plaque techniques. The research method used is a qualitative method. Data collection techniques through observation, interviews and documentation. The results of the study showed that the learning process was carried out systematically through several stages of effective methods. The methods applied include the use of basic drawing as a foundation for skills, a project-based learning approach that encourages student creativity and independence, teachers prepare complete learning media and tools, such as acrylic paint, brushes of various sizes, graphite and colored pencils, and painting media in the form of canvas and sketch paper, to support the teaching and learning process.